Associations Between Essential Elements in Fingernails and Bone Quality in Populations Exposed to Chronic Fluoride in Drinking Water - Kodsup, Pornpimol; Godebo, Tewodros Rango; Nyachoti, Syprose (Exposure and health, 2022)
Many essential/beneficial elements including Ca, Mg, Sr, B, and F − play an important role in bone health. While elevated levels of F − are known to cause adverse health effects on bone, variations of these elements in nails that can be influenced by F − toxicity are unclear. This study aims to assess the relationship between the concentrations of Ca, Mg, Sr, and B in fingernails and bone quality of F − exposed individuals in the Ethiopian Rift Valley. Bone quality was determined using an ultrasonic method that measures the magnitude of speed of sound (SOS) conduction in cortical bones. We collected fingernails of individuals aged 10 to 70 years old (144 males and 123 females) in 25 communities drinking water from wells with F − concentrations ranging from 0.3 to 15.5 mg/L (mean 7 ± 4.7 mg/L). Fluoride concentrations in drinking water were measured using the ion selective electrode (ISE) method. Concentrations of Ca, Mg, Sr, and B in fingernails were measured using Inductively Coupled Plasma Spectrometry (ICP-MS). Mean Ca, Mg, Sr, and B concentrations (mg/kg) in fingernails were 740 ± 425, 98 ± 89, 1.33 ± 1.6, and 0.63 ± 1.2, respectively. Each element was categorized by F − concentrations (mg/L) in drinking water as groups: 1 (< 2), 2 (> 2–6), 3 (> 6–10), and 4 (> 10–15.5). The mean concentrations of these elements in fingernails increased with the increase in F − concentrations in drinking water, and significant differences were observed in the means of groups 1 and 4 for all elements, group 2 for Sr, and group 3 for B. The correlation trends for SOS measurements with these elements in fingernails at different age groups decrease with high F − exposure and the negative associations are more pronounced at older (51–70) ages. These associations suggest F − related bone deterioration in the studied subjects, which is noticeable with the increase in age. The study demonstrates the effect of F − exposure on bone quality, and the studied fingernail elemental variations in populations chronically exposed to F − in drinking water.